Metabolomic and Microbial Remodeling by Shanmei Capsule Improves Hyperlipidemia in High Fat Food-Induced Mice - Du, Lijing; Wang, Qian; Ji, Shuai; Sun, Yuanfang; Huang, Wenjing; Zhang, Yiping; Li, Shasha; Yan, Shikai; Jin, Huizi (Frontiers in Cellular and Infection Microbiology, 2022)
Hyperlipidemia refers to a chronic disease caused by systemic metabolic disorder, and its pathophysiology is very complex. Shanmei capsule (SM) is a famous preparation with a long tradition of use for anti-hyperlipidemia treatment in China. However, the intrinsic regulation mechanism of SM on hyperlipidemia has not been elucidated so far. In this study, a combination of UPLC-Q-TOF/MS techniques and 16S rDNA gene sequencing was performed to investigate the effects of SM treatment on plasma metabolism-mediated change and intestinal homeostasis. The results indicated that SM potently ameliorated high-fat diet induced glucose and lipid metabolic disorders, reduced the histopathological injury. Pathway analysis indicated that alterations of differential metabolites were mainly involved in glycerophospholipid metabolism, linolenic acid metabolism, α-linoleic acid metabolism, arachidonic acid metabolism. These changes were accompanied by significantly perturbation of intestinal microbiota characterized by marked increased microbial richness and changed microbiota composition. There were many genera illustrating strong correlations with hyperlipidemia-related markers (e.g. weight gains, GLU and total cholesterol), including Lachnospiraceae NK4A136 group and Lachnospiraceae NK4B4 group. Overall, this study initially confirmed that hyperlipidemia is associated with metabolic disturbance and intestinal microbiota disorders, and SM can be employed to help decrease hyperlipidemia risk, including improving the abnormal metabolic profile and maintaining the gut microbial environment.